Analisis Tindak Tutur Ilokusi dalam Video “Merdeka Belajar” pada Kanal Youtube KEMENDIKBUD RI - Ayu Febri Anitasari; Alifah Hasna Salsabila; Icca Dyaz Marshanda; Mukhamad Dwi Prasetyo; Yayang Vintoko; Asep Purwo Yudi Utomo; Rizqi Amalia Dwi Asih (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The research focuses on analyzing one part of a speech act, especially illocutions. The author analyzes how illocutions are used in a certain context in the video